Apakah Lp(a) Merupakan Prediktor Kejadian Kardiovaskular Pasca Infark Miokard Akut dengan Elevasi Segmen ST? - Nisa Ike Rini; Manoefris Kasim; Santoso Karo Karo (Jurnal Kardiologi Indonesia, 2007)
Background. The role of lipoprotein (a)/Lp(a) as a risk factor for coronary artery disease has abundantly observed in various prospective and retrospective studies. However there is still lack of evidence about its role in thrombotic process, particularly acute coronary syndrome. Hence, this study was conducted to observe the role of high Lp(a) level on cardiovascular event in post acute ST elevation myocardial infarction (STEMI) patients.Methods and results.A cohort study was conducted by enrolling 110 STEMI patients (mean age 53.3 ± 8 years) eligible for fibrinolytic therapy. Respondents were observed from January 2003 to May 31st 2005 (average observation period was 432 days). Recurrent angina, reinfarction, revascularization within 6 months after admission and death were defined as end points of the study. Lp(a) measurement were done from blood sample taken within 24 hours after onset of infarction. Respondents were divided into three groups according to level of Lp(a) percentiles. The highest percentile (> 75%) was (Lp(a) level of > 26.4 mg/dL) and the lowest percentile (<25%) was (Lp(a) level of < 7.2 mg/dL Survival analysis of composite cardiovascular events showed that the highest percentile group failed to show lower cumulative survival compared to the lowest percentile group; hazard ratio of 0.69 (95% CI 0. 29-1.63; p=0. 40). This phenomena was also observed in survival analysis of death; hazard ratio of 0.92 (95% CI 0.13-6.58; p=0.190).Conclusions. It was concluded that high level of Lp(a) was not a predic-tor of cardio-vascular event following acute STEMI.